Esther’s Psychopath Behavior In The Orphan Movie - M. Irsyad Rasyid Rusyidi; Mamik Tri Wedawati (Fakultas Bahasa dan Budaya Asing (FBBA), Universitas Muhammadiyah Semarang, 2022)
A psychopathic condition is a psychological behavior that has long been regarded as destructive and bad for society. The purpose of this study is to identify the characteristics of Ester's psychopathic problem, as well as the reasons that cause Ester, the main character in the film The Orphan, to become a psychopath. The analysis data are derived from the film The Orphan, the script, and the cinematography. Using psychopathy theory, the evidence is interpreted. To answer the research problem, the writer employs psychological theory from Wellek and Warren (1956), which is combined with psychoanalysis theory from Sigmund Freud and James D. Page. The qualitative descriptive approach is used in this study. The research findings reveal two issues: Esther's psychopathic disorders and the factors that cause Esther to become a psychopath. According to the research findings, Esther's character is a psychopath. First, there are five psychopath behaviors: liar, lack of feeling guilty, lack of empathy, manipulative, and aggressive. Second, Esther becomes a psychopath due to two factors: biological and environmental.Keywords: Psychopath, Behaviour, Movie